2021
DOI: 10.1002/mame.202100761
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach to Sulfur‐Rich Covalent Organic Frameworks for Selective Recovery of Trace Gold

Abstract: As one of the most precious metals with versatile uses, the global production needs of gold are much larger than its deposits. Therefore, it is imperative to recover gold from secondary sources so as to realize resource reuse and environmental protection. Due to the desirable physicochemical properties, covalent organic frameworks (COFs), especially the thiol/thioether-functionalized sulfur-rich COFs with strong affinity for Au ions, have exhibited promising prospects for gold recovery. However, their applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This indicated that the gold adsorption process on TTASDFP was chemisorption, which is most likely a result to the Au−S chelation. 53,71 Additionally, the gold uptake at different concentrations was evaluated. The adsorption isotherm (Figure 3b) displayed an increased adsorption amount with an increase in the Au 3+ concentration, with the maximum uptake reaching approximately 245 mg•g −1 at a relatively high concentration of 300 ppm.…”
Section: Characterization Of Ttasdfpmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicated that the gold adsorption process on TTASDFP was chemisorption, which is most likely a result to the Au−S chelation. 53,71 Additionally, the gold uptake at different concentrations was evaluated. The adsorption isotherm (Figure 3b) displayed an increased adsorption amount with an increase in the Au 3+ concentration, with the maximum uptake reaching approximately 245 mg•g −1 at a relatively high concentration of 300 ppm.…”
Section: Characterization Of Ttasdfpmentioning
confidence: 99%
“…79 In addition, the gold interaction with the sulfur moieties was confirmed by the decrease of the overall S 2p signal by ∼1 eV pos-goldadsorption, which is parallel to what was observed for other reported S−Au 3+ systems (Figure 5b). 53 Moreover, curvefitting analysis of the S 2p signal showed that the spectra had two deconvoluted peaks assigned as S 2p 3/2 and S 2p 1/2 , which were attributed to sulfur atoms bound and unbounded gold atoms, respectively (Figure . 5c,d).…”
Section: Characterization Of Ttasdfpmentioning
confidence: 99%
See 2 more Smart Citations
“…22C). 174 In order to remove BTEX (benzene, toluene, ethyl benzene, and xylenes) and Hg(II) ions simultaneously from water, a novel thiol-functionalized covalent organic framework (COF-S-SH) was prepared by Li and coworkers (Fig. 23A).…”
Section: Polymer Chemistry Reviewmentioning
confidence: 99%